Feedback on Escape Behavior of Birds Under Different Hunger Pressure - Xiao‐Yang Bao; Jia‐Jia Xin; Yuan‐Xing Ye; Can‐Shi Hu (Ecology and Evolution)
ABSTRACT The risk of predation has always been a significant impact on wild birds. Birds, facing with limited energy, must balance their investment between foraging and vigilance. There were currently limited understandings of the vigilant behavior feedback of birds under different hunger pressure. Therefore, we employed the White‐browed laughingthrush (Pterorhinus sannio) and White wagtail (Motacilla alba) as research subjects to carry out experiments in winter, in exploring the tolerance of birds to external stress under different hunger pressure. After a night of energy expenditure, individuals of both species faced greater hunger pressure in the morning. The results of general linear models showed that the flight initiation distance (FID) of both species in the morning (7:00–9:00) was significantly shorter than that in the evening (16:00–18:00). Additionally, when the weather was cold (daily minimum temperature ≤ 5°C), the FID of the White‐browed laughingthrush and White wagtail was significantly shorter in the morning, as same as the results of general linear models. However, when the weather was warm (daily minimum temperature ≥ 10°C), there was no significant difference even though the FID average of both species was shorter in the morning than in the evening. These suggested that the consumption and supplementation of energy are very important for birds, as the higher their hunger pressure, the greater their willingness to forage and take on risk, especially in cold winter.